2006
DOI: 10.1111/j.1572-0241.2006.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Past HBV Viral Load as Predictor of Mortality and Morbidity from HCC and Chronic Liver Disease in a Prospective Study

Abstract: In this prospective study, viral load is associated with increased mortality from HCC and CLD in HBV-infected subjects. Viral load may be a useful prognostic tool in HBV infection, and interventions aimed at its reduction should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(186 citation statements)
references
References 26 publications
10
169
1
6
Order By: Relevance
“…Participants with persistent elevation of serum HBV DNA level during follow-up had the highest HCC risk. These results were consistent with another prospective cohort study in 2,763 adult HBV carriers with 11 years of follow-up from Haimen city in China that assessed the relationship between HBV viral load at entry and mortality [34]. Compared to HBV carriers without detectable viremia, the relative risk for HCC mortality in those with low viral load (£2 · 10 4 IU/ml) was 1.7 (95% CI, 0.5-5.7) and 11.2 (95% CI, 3.6-35.0) in those with high viral load ( ‡2 · 10 4 /ml).…”
Section: Serum Hbv Dna Levelsupporting
confidence: 91%
“…Participants with persistent elevation of serum HBV DNA level during follow-up had the highest HCC risk. These results were consistent with another prospective cohort study in 2,763 adult HBV carriers with 11 years of follow-up from Haimen city in China that assessed the relationship between HBV viral load at entry and mortality [34]. Compared to HBV carriers without detectable viremia, the relative risk for HCC mortality in those with low viral load (£2 · 10 4 IU/ml) was 1.7 (95% CI, 0.5-5.7) and 11.2 (95% CI, 3.6-35.0) in those with high viral load ( ‡2 · 10 4 /ml).…”
Section: Serum Hbv Dna Levelsupporting
confidence: 91%
“…Yang et al [6] reported that the incidence of HCC was significantly higher in those who were HBsAg and HBeAg positive than in those who were HBsAg positive only. Recently, this was confirmed by showing a correlation between baseline HBV DNA levels in asymptomatic adult HBsAg carriers and the risk of HCC [10][11][12][13].…”
Section: Hepatitis B Infectionmentioning
confidence: 83%
“…Its results have been replicated in a second study that was also conducted in Chinese patients. 82 The relationship between viral load and liver disease outcome has been found in other studies around the world including West Africa, China, and Japan, but primarily in Asians.…”
Section: Limitationsmentioning
confidence: 87%